Oxidative dehydrogenation in complexes of transition metals (Cu(II), Co(II), Ni(II)) with N,N '-di(2-hydroxybenzyl)diamines - (:unkn) unknown (MAIK NAUKA/INTERPERIODICA, 2001)
Potentially tetradentate ligands N,N ' -di(2-hydroxybenzyl)ethylenediamine (L-1) and N,N ' -di(2-hydroxybenzyl)o-phenylenediamine (L-2) and complexes of Cu(II), Co(II), and Ni(II) with L-1 and L-2 were synthesized. The EPR and electronic spectroscopy methods were used to reveal the octahedral structure of the Cu(II) complex with L-1 in the solid state. In water-alcohol solutions, the Cu(II) and Ni(II) complexes with both ligands have distorted octahedral structures. The Co(II) complexes form dioxygen adduct with L-1. In the presence of oxygen, the ligands in the obtained complex compounds can undergo oxidative dehydrogenation with selective formation of the respective disalicylaldimines. In the case of L-2, the oxidative dehydrogenation is observed for the complexes of all studied metals in comparatively mild conditions (T = 30 degreesC, methanol and other solvents), while in the case of L-1, it occurs only with the Co(II) complexes in the presence of pyridine.
Keywords: MACROCYCLIC LIGANDS; MOLECULAR-OXYGEN; TETRACYANOFERRATE(II); RUTHENIUM(II); 1,2-DIAMINES; COBALT(II); PRODUCTS; AMINES